Antagonistic managers, careless workers and extraverted salespeople: an examination of personality in occupational choice - Roger Ham; P. N. (Raja) Junankar; Robert Wells (Institute for the Study of Labor (IZA), 2009)
This paper is an econometric investigation of the choice of individuals between a number of occupation groupings utilising an extensive array of conditioning variables measuring a variety of aspects of individual heterogeneity. Whilst the model contains the main theory of occupational choice, human capital theory, it also tests dynasty hysteresis through parental status variables. The focus is an examination of the relationship between choice and personality with the inclusion of psychometrically derived personality variables. Occupational choice is modelled using multinomial logit estimation using the Household Income and Labour Dynamics in Australia (HILDA) survey data. Human capital variables are found to exhibit strong credentialism effects. Parental status has a small and limited effect on occupation outcomes indicative of only some small dynasty hysteresis. On the other hand, personality effects are found to be significant, relatively large and persistent across all occupations. Further, the strength of these personality effects are such that they can in many instances rival that of various education credentials. These personality effects include but are not limited to: managers being less agreeable and more antagonistic; labourers being less conscientiousness; and sales people being more extraverted.
urn:nbn:de:101:1-2009061585
Keywords: J24; J62; C25; 330; Occupational choice; personality traits; credentialism; dynasty hysteresis; Berufswahl; Persönlichkeitspsychologie; Familiensoziologie; Bildungsforschung; Schätzung; Australien